1999
DOI: 10.1038/sj.onc.1202606
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitogenicity of an αβ heterodimeric PDGF receptor complex correlates with lack of RasGAP binding

Abstract: The dierent platelet-derived growth factor (PDGF) isoforms cause activation of their a and b protein tyrosine kinase receptors through dimerization. Homodimerization as well as heterodimerization of receptors occur. It has been shown previously that the heterodimeric receptor complex mediates a stronger mitogenic response than either of the homodimeric complexes. In this report, we show that in cells expressing both PDGF a-and b-receptors, stimulation with PDGF-AB, which leads to preferential heterodimer forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…6 PDGFR-aa, PDGFR-ab, and PDGFR-bb transduce a variety of cellular signals that act to prevent apoptosis (survival signaling), stimulate mitogenesis (proliferative signaling), stimulate cellular chemotaxis, and increase the concentration of intracellular calcium. [12][13][14] These effects are mediated through several well characterized downstream signaling cascades induced by the activation of PDGFRs, including the Ras/mitogen-activated protein kinase (MAPK) pathway, the phosphatidylinositol 3-kinase (PI3-K) pathway, and the phospholipase C-c1 (PLC-c1) pathway. The PI3-K pathway is critical for PDGF-induced prevention of apoptosis, actin reorganization, and cell migration.…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
“…6 PDGFR-aa, PDGFR-ab, and PDGFR-bb transduce a variety of cellular signals that act to prevent apoptosis (survival signaling), stimulate mitogenesis (proliferative signaling), stimulate cellular chemotaxis, and increase the concentration of intracellular calcium. [12][13][14] These effects are mediated through several well characterized downstream signaling cascades induced by the activation of PDGFRs, including the Ras/mitogen-activated protein kinase (MAPK) pathway, the phosphatidylinositol 3-kinase (PI3-K) pathway, and the phospholipase C-c1 (PLC-c1) pathway. The PI3-K pathway is critical for PDGF-induced prevention of apoptosis, actin reorganization, and cell migration.…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
“…The PDGF-AB isoform has been reported to possess the strongest ability to induce a mitogenic response in cells expressing both a-and b-receptors (Heidaran et al, 1991;Rupp et al, 1994). We have therefore investigated the possible unique features of the heterodimeric PDGF receptor complex compared to the homodimeric complexes, and found that in the heterodimeric complex activation of Ras and Erk2 MAP kinase were stronger and more sustained compared to homodimeric complexes (Ekman et al, 1999). We could, furthermore, show that phosphorylation of Tyr771, the RasGAP association site in the PDGF b-receptor, occurred to a much lower extent in the ab heterodimer than in bb homodimers.…”
Section: Introductionmentioning
confidence: 99%
“…Stable transfectants were obtained by selection with puromycin (Calbiochem) at a concentration of 0.5 mg/ml. PAE/a, PAE/b and PAE/bY763F/Y1009F as well as PAE/ab cells have been described earlier (Ekman et al, 1999;Mori et al, 1993;RoÈ nnstrand et al, 1999;Yokote et al, 1996). PAE cells were maintained in Ham's F-12 medium supplemented with 10% fetal calf serum (FCS).…”
Section: Plasmids Cells and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, through recruitment of the Ras guanine nucleotide exchange factor Sos1, Grb2 directs phosphotyrosineinduced exchange of GDP for GTP on Ras, thereby stimulating the Erk MAPK pathway (3). RasGAP and Grb2 are therefore SH2-containing proteins with opposing effects on the state of Ras activation, and data from both invertebrate and mammalian systems suggest that RTKs potentially employ Grb2 and RasGAP in combination to achieve sophisticated regulation of the Ras signaling pathway (14,15). SH2 domains generally bind short phosphotyrosine-containing peptide sequences but differ in their ability to recognize residues C-terminal to the phosphotyrosine (7,16,17).…”
mentioning
confidence: 99%